Activation of Hes1 and Msx1 in transgenic mouse embryonic stem cells increases differentiation into neural crest derivatives - Mendez Maldonado, Karla (2018)
The neural crest (NC) comprises an ectodermal multipotent cell population that produces peripheral neurons, cartilage and smooth muscle cells, among other phenotypes. The participation of Hes1 and Msx1 when expressed in mouse embryonic stem cells (mESCs) undergoing NC differentiation is unexplored. In this work, we generated stable mESCs transfected with constructs encoding chimeric proteins in which the ligand binding domain of glucocorticoid receptor (GR), which is translocated to the nucleus by dexamethasone addition, is fused to either Hes1 (HGR) or Msx1 (MGR), as well as double-transgenic cells (HGR+MGR). These lines continued to express pluripotency markers. Upon NC differentiation, all lines exhibited significantly decreased Sox2 expression and upregulated Sox9, Snai1 and Msx1 expression, indicating NC commitment. In parallel experiments, dexamethasone was added to induce nuclear translocation of the chimeric proteins at early stages, and we found that Collagen IIa transcripts were increased in MGR cells, whereas coactivation of HGR+MGR caused a significant increase in Smooth muscle actin (alpha-Sma) transcripts. Immunostaining showed that activation in HGR+MGR cells induced higher proportions of BETA-TUBULIN III+ and alpha-SMA+ cells. These findings indicate that nuclear translocation of MSX1 might be used to produce chondrocytes at higher efficiencies, but simultaneous activation of HES1 and MSX1 increases the generation of smooth muscle and neuronal cells.